2014
DOI: 10.1007/s00603-014-0674-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water on the Deformation and Failure of Rock in Uniaxial Tension

Abstract: To design and construct underground structures, it is essential to understand the mechanical properties of rock in not only compression but also tension. It is well known that water is one of the important factors affecting the deformation and failure of rock. In this study, laboratory tests and numerical simulations were conducted to understand the effect of water on rock properties in uniaxial tension. In the experiments, a testing machine previously used for uniaxial tension tests in dry conditions was modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(50 citation statements)
references
References 21 publications
8
41
1
Order By: Relevance
“…To validate the test set-up, some preliminary tests were carried out on ostensibly homogeneous samples of Blackhill Quarry sandstone (lacking visible fabric), using a similar set-up to that of Okubo and Fukui (1996) and Hashiba and Fukui (2014). Four strain gauges (10 mm in length) were attached to the middle of the specimens.…”
Section: Testing Apparatus Set-up and Verificationmentioning
confidence: 99%
“…To validate the test set-up, some preliminary tests were carried out on ostensibly homogeneous samples of Blackhill Quarry sandstone (lacking visible fabric), using a similar set-up to that of Okubo and Fukui (1996) and Hashiba and Fukui (2014). Four strain gauges (10 mm in length) were attached to the middle of the specimens.…”
Section: Testing Apparatus Set-up and Verificationmentioning
confidence: 99%
“…De et al (2005) conducted axial compression experiments with Carrara marble with and without water, and these authors found water-soaked specimens to be slightly weaker than dry specimens. Hashiba and Fukui (2014) researched the tensile strength of granite under wet conditions and its weakening mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable number of studies have been carried out to investigate the influence of water content on mechanical properties and failure characteristics of coal and rock mass [7][8][9][10][11][12]. According to former studies, the uniaxial compressive strength, elastic modulus, and tensile strength of the rock all decline as moisture content increases.…”
Section: Introductionmentioning
confidence: 99%